Peran Sistem Lingkungan Dalam Pembentukan Resilience Pada Anak Miskin (Role of Ecological System In Formation of Resilience of Poor Childrenon Child Poverty - Annisah, Annisah (Jurnal Ilmu Kesejahteraan Sosial, 2014)
Previous studies showed that a person’s resilience is affected by many factors. Poverty is considered to be one of the factors that can interfere a person’s resilience. Resilience at every age is different, the resilience in adults and children is also different. Furthermore, it is interesting to explore resilience of poor children and the role of the system environment in which children live. This study used a qualitative approach with call life history method in 4 families of scavengers in Depok . Techniques used in data collection are in-depth interviews about child’s life from childhood to present, observations, and ecomaps to analyse data. Analysis showed that resilience of poor children was strongly